Developing a make or buy strategy for manufacturing business - Probert, David Dr. (London, United Kingdom Institution of Electrical Engineers, 1997)
The issues surrounding the make or buy question in manufacturing industry are as old as the manufacturing activity itself, and interest in finding a sound way of dealing with them has been a constant feature of industrial life. This book represents the results of a research and application project carried out by the author while an industrial research fellow, based in the Manufacturing Engineering Group at the University of Cambridge, and supported by Lucas Industries and the Royal Academy of Engineering. As an area for research, make or buy issues are a central part of the manufacturing strategy of a business, which is a core research theme at the Cambridge Manufacturing Group. Other Group research interests include the management of technology, new product introduction, performance measurement and international manufacturing. All programmes are carried out with the active involvement of manufacturing industry, with the aim of transferring practical new approaches to dealing with these issues to participating companies and beyond. The team based approach to formulating a new make or buy strategy described in this book has been applied in many different businesses and provides a clear and practical route to improving manufacturing performance.
Electronic reproduction.
Keywords: Manufacturing industries; Manufactures; Production management; Production control; Electronic books